Rheological indexes of sauces using okara in canned meat - Strashynskyi, Igor; Pasichnyi, Vasyl; Bakhmach, Volodymyr; Grabarovskyi, Andriy (My University, 2018)
Sauce is an additional ingredient of food that has a characteristic stiff consistency used in the preparation of dishes or is served to the finished food to improve its taste and aroma.
Keywords: кафедра технології м’яса і м’ясних продуктів; sauces; improvement of taste and aroma